2002
DOI: 10.1103/physrevb.65.172502
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting energy gap in aMgB2film observed by infrared reflectance

Abstract: Far-infrared reflectance of a MgB2 film has been measured by Fourier-transform spectroscopy for frequencies 10 cm −1 < ν < 4000 cm −1 above and below the superconducting transition. The data provide clear experimental evidence for the onset of a superconducting gap at 24 cm −1 at T = 5 K. On increasing temperature the gap energy increases, contrary to what is expected in isotropic BCS superconductors. The small zero-temperature gap value and its unconventional increases on increasing temperature can only be ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
27
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 31 publications
6
27
0
1
Order By: Relevance
“…In addition, the reflectance for the frequency range 4 cm −1 Ͻ Ͻ 40 cm −1 has been calculated using the complex conductivity data, obtained by the transmittance technique described above. The combination of the results from two experimental techniques 36 substantially expands the low-frequency limit of the available spectrum and the quality of the subsequent Kramers-Kronig transformation. Figure 1 shows the complex reflectance and transmittance of magnetite in the vicinity of the Verwey transition.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the reflectance for the frequency range 4 cm −1 Ͻ Ͻ 40 cm −1 has been calculated using the complex conductivity data, obtained by the transmittance technique described above. The combination of the results from two experimental techniques 36 substantially expands the low-frequency limit of the available spectrum and the quality of the subsequent Kramers-Kronig transformation. Figure 1 shows the complex reflectance and transmittance of magnetite in the vicinity of the Verwey transition.…”
Section: Methodsmentioning
confidence: 99%
“…It has recently been noted that the gap seen in optical conductivity appears to be very small [24,25]. We calculated the anisotropic analog of the Mattis-Bardeen conductivity [26] averaged over all directions, which should correspond to the response of a polycrystalline thin film sample as has been used in Refs.…”
mentioning
confidence: 99%
“…The spectra were taken down to 3 meV while changing temperature down to 1.6 K and applying magnetic fields up to 7 T, which allowed a fully optical determination of the temperature dependence of the c-axis critical field H c2 (∼ 5 T at lowest 1.6 K). The authors [46] observed the absorption threshold at about ∼ 4 meV, which is close to the observation on thin films [52,49]. Di Castro et al [24] measured the ratio R S /R N on separate ab-oriented single crystals of MgB 2 (T c =38.5 K) using the synchrotron radiation between 3 and 12 meV to compensate the loss of signal due to the small sample size.…”
Section: Far-infrared Spectra: One Gap or Two?mentioning
confidence: 75%
“…Further experiments on thin films [49,50,51,52,53,54], thick films [18], single crystals [46,24] and dense polycrystals [19,55] provided much more detailed and quantitative spectral information that in general supported such assignment ( Table 1). Note that this gap value gives an anomalously small ratio 2∆/k B T c ∼ 1 − 2 as compared to the weak-coupling BCS result of 3.52.…”
Section: Far-infrared Spectra: One Gap or Two?mentioning
confidence: 87%
See 1 more Smart Citation